Lightweight coordinated defence against interest flooding attacks in NDN - Salah, Hani; Wulfheide, Julian; Strufe, Thorsten (IEEE, 2015)
Named-Data Networking (NDN) is a promising architecture for future Internet. However, routers and content providers in NDN can be targets for a new DDoS attack called the Interest Flooding Attack (IFA). As a consequence, affected routers drop legitimate interest packets. We argue that IFA can be defended effectively when it is detected and mitigated, at early stage, based on timely and aggregated information of exchanged packets and forwarding states. Towards this end, we adapt CoMon, a framework that we developed formerly to coordinate caching-related decisions in NDN. This choice is motivated by CoMon's proven ability to realize efficient, yet lightweight, coordination. A preliminary evaluation confirms the effectiveness of our solution against IFAs.
Keywords: Monitoring, Internet, Conferences, Computer crime, Routing, Systems architecture, Topology